Effects of post-washing on pretreated biomass and hydrolysis of the mixture of acetic acid and sodium hydroxide pretreated biomass and their mixed filtrate. (November 2021) - Zhao, Jikai; Yang, Yang; Zhang, Meng; Wang, Donghai
Highlights: Post-washing alters chemical characteristics of HOAc and NaOH pretreated biomass. HOAc and NaOH pretreated filtrate is mixed as a buffer to reduce water consumption. One-volume water is sufficient to wash pretreated biomass without conceding sugar yield. Glucose concentration has a quadratic correlation with solid loading used for hydrolysis. Abstract: Effects of post-washing [one-volume water (I-VW) or double-volume water (Ⅱ-VW)] on pretreated hemp and poplar biomass and enzymatic hydrolysis of the mixture of HOAc and NaOH pretreated biomass and their mixed filtrate were investigated. Compared to I-VW, Ⅱ-VW increased 3.76–6.80% of glucan content in NaOH pretreated biomass, diminished lignin recondensation, and heightened cellulose-related FTIR peak intensities, crystallinity index, and lignin removal. The pH of mixed filtrate was around 4.80, precipitating the NaOH soluble lignin partially. Although Ⅱ-VW showed lower lignin recoveries than I-VW, their FTIR characteristics were equivalent to the commercial alkali lignin. Enzymatic hydrolysis at solid loadings of 2.5–10% (w/v) demonstrated that I-VW and Ⅱ-VW had marginal variations in sugar concentration and conversion efficiency, indicating that I-VW is sufficient for post-washing pretreated biomass. Glucose concentration exhibited a quadratic correlation with solid loading and hemp biomass reached the maximum glucose (43.88 g/L) and total sugar (57.08 g/L) concentrations with I-VW.